Microbiological and Hedonic Test of Lanolin Listick with the Addition of Rosella Flower (Hibiscus sabdariffa L) Extract Dye - Nur'Aeni, Nopi; Vivi Indriani (Jurnal Peternakan Integratif, 2024)
Lanolin fat is produced from processing sheep wool. Lanolin is one of the ingredient for processing lipstick. a solid bar-shaped cosmetic preparation, serves as a lip colorant in makeup. Lanolin lipstick, still in need of innovation, for example in colour. Organic colouring can use, among other things, colours from Rosella flowers (Hibiscus sabdariffa L). The purpose of this study is to look at the microbiological and sensory properties of lanolin lipstick that has different amounts of Rosella flower extract (Hibiscus sabdariffa L) added to it. This study used a completely randomized design (CRD) unidirectional pattern with four treatments, namely, 0%, 20%, 40%, and 60% levels of Rosella flower extract. The data obtained were analyzed by ANOVA (analysis of variance) to determine the effect of each treatment, and if the data showed differences with a significant level of 95%, then Tukey's multiple comparison test was carried out. The study found that adding different amounts of Rosella flower extract to lanolin lipstick did not have a significant effect (P > 0.05) on the total plate count (ALT) of lipstick during storage. However, it did have a significant effect (P< 0.05) on the hedonic test and hedonic quality of color parameters. In conclusion, the addition of 60% rosella flower extract to lanolin lipstick is able to suppress bacterial growth during the lipstick storage process. Rosella flower extract affects the colour of the lipstick which is getting redder, the aroma of the extract is stronger, the texture is smooth.